STATISTICAL ANALYSIS OF FOODS CONSUMPTION BY THE UKRAINIAN POPULATION - Кисельов, К. Ю. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
Economic change and political reforms taking place in Ukraine require detailed data allowing for robust analysis of the population living standards, particularly ones on the consumption of foods. Existing methodologies for statistical analysis of foods consumption require improvements. A method proposed by the author is based on statistical measurement of foods consumption using official statistical data (for 2005–2012) on aggregate income and aggregate expenses of the Ukrainian population, structure of aggregate expenses by consumption purpose, consumption of foods by category of foods.